The Determination of Compensation, Non-Physical Work Environment, and Loyalty on Employee Performance - Desty Febrian, Wenny; Rianggara, Rahata (International Journal of Psychology and Health Science, 2023)
This research aims to determine and analyze the influence of compensation, non-physical environment, and employee loyalty on employee performance. This type of research is associative research. The instrument of this research is a questionnaire with a Likert scale. The population in this study was all 100 employees. Saturated sampling technique. The number of samples required in this research is 100 people. Data collection techniques in this research are literature study, observation, questionnaires, and interviews. The testing technique used is multiple linear regression with results Y = 2.002 + 0.103 (X1) + -0.052 (X2) + 0.896 (X3) and hypothesis testing consisting of the t-test and f-test. The results of this research are: (1) The positive and insignificant influence of compensation on employee performance is shown by the calculated t value of 1.855 < 1.984. (2) There is a negative and insignificant influence between the non-physical work environment on employee performance as shown by the calculated t value of -993 < 1.984. (3) There is a positive and significant influence between employee loyalty and employee performance as shown by the calculated t value of 9.685 > 1.984. (4) There is a positive and significant influence between compensation, non-physical work environment, and loyalty on employee performance as shown by the calculated f value of 112.982 > 2.70. The correlation coefficient (R) is 0.883, which means the relationship between variables is quite strong and the coefficient of determination is 0.779, which means 77.9% of the three independent variables influence employee performance simultaneously and the rest is influenced by other variables. The correlation coefficient (R) is 0.883 which means that the closeness between variables is quite strong and the coefficient of determination is 0.779 which means that 77.9% of the three independent variables simultaneously affect employee performance and the rest is influenced by other variables.